Evaluation of the odd-even effect in limits of detection for electron microprobe analysis of natural minerals - Verma, Surendra P.; Pandarinath, Kailasa; Velasco Tapia, Fernando; Rodríguez Ríos, Rodolfo (Elsevier, 2009)
Limit of detection (LOD), being a fundamental quality parameter for analytical techniques, has been recently investigated and a systematic behavior has been observed for most odd–even element pairs for many techniques. However, to the best of our knowledge very few LOD data are available in published literature for electron microprobe analysis; these consist of three papers, two being on rare-earth elements and the third covering a large number of elements of atomic number between 21 and 92. These data confirm the systematic behavior of LODs for many odd–even pairs. To initiate to full this gap, we determined LODs for several major rock-forming chemical elements from Na to Fe with atomic numbers between 11 and 26, during the microprobe analysis of common minerals (olivine, plagioclase, pyroxene, amphibole, quartz, and opaques) in volcanic rocks. The odd–even effect of nuclear stability seems to be present in LOD data for most odd–even pairs investigated. Nevertheless, the experimental strategy concerning the reference materials, calibration procedure, and blank measurements, should be substantially modified to better evaluate the systematic behavior of LOD values in microprobe analysis.